The Quantification of Radiation Damage in Orthophosphates Using Confocal μ-Luminescence Spectroscopy of Nd3+ - Lenz, Christoph; Thorogood, Gordon; Aughterson, Robert; Ionescu, Mihail; Gregg, Daniel J.; Davis, Joel; Lumpkin, Gregory R. (Frontiers in Chemistry, 2019)
In this study, we present a new concept based on the steady-state, laser-induced photoluminescence of Nd3+, which aims at a direct determination of the amorphous fraction fa in monazite- and xenotime-type orthophosphates on a micrometer scale. Poly-crystalline, cold-pressed, sintered LaPO4 and YPO4 ceramics were exposed to quadruple Au-ion irradiation with ion energies 35 MeV (50% of the respective total fluence), 22 MeV (21%), 14 MeV (16%), and 7 MeV (13%). Total irradiation fluences were varied in the range 1.6×1013 − 6.5 ×1013 ions/cm2. Ion-irradiation resulted in amorphization and damage accumulation unto a depth of ~ 5 µm below the irradiated surfaces. The amorphous fraction created was quantified by means of surface-sensitive grazing-incidence X-ray diffraction and photoluminescence spectroscopy using state-of-the-art confocal spectrometers with spatial resolution in the μm range. Monazite-type LaPO4 was found to be more susceptible to ion-irradiation induced damage accumulation than xenotime-type YPO4. Transmission electron microscopy of lamella cut from irradiated surfaces with the focused-ion beam technique confirmed damage depth-profiles with those obtained from PL hyperspectral mapping. Potential analytical advantages that arise from an improved characterization and quantification of radiation damage (i.e., fa) on the µm-scale are discussed.